Effects of an amylopectin and chromium complex on the anabolic response to a suboptimal dose of whey protein. Issue 1 (8th February 2017) - Ziegenfuss, T. N.; Lopez, H. L.; Kedia, A.; Habowski, S. M.; Sandrock, J. E.; Raub, B.; Kerksick, C. M.; Ferrando, A. A.
Abstract: Background: Previous research has demonstrated the permissive effect of insulin on muscle protein kinetics, and the enhanced insulin sensitizing effect of chromium. In the presence of adequate whole protein and/or essential amino acids (EAA), insulin has a stimulatory effect on muscle protein synthesis, whereas in conditions of lower blood EAA concentrations, insulin has an inhibitory effect on protein breakdown. In this study, we determined the effect of an amylopectin/chromium (ACr) complex on changes in plasma concentrations of EAA, insulin, glucose, and the fractional rate of muscle protein synthesis (FSR). Methods: Using a double-blind, cross-over design, ten subjects (six men, four women) consumed 6 g whey protein + 2 g of the amylopectin-chromium complex (WPACr) or 6 g whey protein (WP) after an overnight fast. FSR was measured using a primed, continuous infusion of ring-d5 -phenylalanine with serial muscle biopsies performed at 2, 4, and 8 h. Plasma EAA and insulin were assayed by ion-exchange chromatography and ELISA, respectively. After the biopsy at 4 h, subjects ingested their respective supplement, completed eight sets of bilateral isotonic leg extensions at 80% of their estimated 1-RM, and a final biopsy was obtained 4 h later. Results: Both trials increased EAA similarly, with peak levels noted 30 min after ingestion. Insulin tended ( p = 0.09) to be higher in the WPACr trial. Paired samples t-tests using baseline and 4-h post-ingestion FSR data separately for each group revealed significant increases in the WPACr group (+0.0197%/h, p = 0.0004) and no difference in the WP group (+0.01215%/hr, p = 0.23). Independent t-tests confirmed significant ( p = 0.045) differences in post-treatment FSR between trials. Conclusions: These data indicate that the addition of ACr to a 6 g dose of whey protein (WPACr) increases the FSR response beyond what is seen with a suboptimal dose of whey protein alone.